Anahita's Woven Riddle - Sayres, Meghan Nuttall (Harry N. Abrams, Inc., 2006)
In this enchanting historical novel, a nomad in nineteenth-century Iran takes fate into her own hands when her father promises her in marriage to a man she dislikes. Anahita convinces her father to let her hold a contest in which potential suitors must correctly answer the riddle she has woven into her wedding carpet. A diplomat, a schoolteacher, a shepherd, and a prince compete in Anahita's battle of wits for the heart of this extraordinary girl.
Keywords: Juvenile Fiction; Middle East; People and Places